LabVIEW-based speed and voltage control of synchronous generator - Chen, Xuebing. (2013)
With an increasing requirement for power quality, frequency and voltage control become very important in power system control. In this project, the micro-grid has been equipped with Load Frequency Control (LFC) and Optimal Power Flow (OPF) which have been coded with LabVIEW. A newly arrived synchronous generator cannot be controlled by LFC and OPF directly. This project aims to design a speed governor module for the synchronous generator to fulfill the real power control of this generator. Another aspect of the project is to install an automatic voltage regulator (AVR) to regulate the generator terminal voltage to maintain its terminal voltage. Thus the generator will be able to contribute when it is connected to the micro-grid. The methodology was divided into two parts which are software development and hardware implementation. LabVIEW was chosen to code the program, and a PID controller was used in the program. The software development consists of design of the program, PID controller tuning and simulation. However, the program which worked well in simulation was not realized on hardware for some hardware problems. The AVR was also not installed because the speed control had not been achieved. Program improvement and hardware implementation are suggested in future work.